Shear fatigue behavior of AW2099-T83 aluminum-lithium alloy. (December 2018) - Adinoyi, Muhammed J.; Merah, Nesar; Albinmousa, Jafar
Highlights: Strain-controlled shear fatigue behavior of AW2099-T83 aluminum lithium alloy. An elastic to plastic hysteresis loop evolution. A regression-based analysis of the plastic strain and plastic energy evolution with number of cycles. A comparative assessment of the fatigue parameters of the investigated alloy with traditional aluminum alloys. Microscopic analysis of crack profile and fracture surface. Abstract: Monotonic shear and strain-controlled shear fatigue behavior of AW2099-T83/SHP Aluminum-Lithium alloy were investigated. Torsion fatigue testing was performed at strain amplitudes ranging from 0.5% to 1.5%. The material strain hardened under monotonic shear loading but cyclically softened after few fatigue cycles for all the ranges of applied strain amplitudes. Under torsion fatigue, macroscopic plastic deformation was observed only for strain amplitudes higher than 0.7%. Cyclic plastic strain was found to increase with the number of cycles and the mean stress remained very small during most of the specimen life. Coffin-Manson relation was used to determine the shear fatigue constants of the material. The developed properties were used to arrive at a good correlation between estimated and experimental fatigue life under shear strain loading. The shear fatigue properties were compared to values reported for traditional Al alloys 2xxx, 6xxx and 7xxx series in axial fatigue after the conversion of the shear fatigue parameters to axial equivalent. The surface crack paths were observed to be mostly in the longitudinal direction with a 90° bifurcation at low strain amplitudes. Resulting crack morphologies were analyzed by SEM.